Usefulness of fetal renal length in the prediction of gestational age - Reyna-Villasmil, Eduardo (2023)
Objective: To establish the usefulness of fetal kidney length measurement in theprediction of gestational age. Design: Prospective, longitudinal cohort study.Institution: Hospital Central "Dr. Urquinaona", Maracaibo, Venezuela. Participants:Women with low-risk singleton pregnancies, between 18 and 40 weeks of gestation.Methods: Biparietal diameter, abdominal circumference, femur length, and fetalkidney length were measured during the duration of pregnancy. Main outcomemeasures: Prediction of gestational age by measurement of fetal kidney length.Results: Data from 215 pregnant women was selected. A total of 3,291 total evaluationswere performed, with the lowest number of evaluations at 31 weeks (128), and thehighest number (157) at 28 weeks. Fetal kidney length presented strong, positiveand significant correlations with gestational age by date of last menstrual period andby ultrasound measurements (p < 0.001). The model of gestational age predictedby the transverse diameter of the cerebellum reached a value of the coefficientof determination of 0.682. The correlation between gestational age by date of lastmenstrual period and that predicted by the model reached a value of r = 0.826(p < 0.001). Conclusion: Measurement of fetal kidney length is useful for predictinggestational age and together with other routine ultrasound measurements mayimprove the ability of current prediction models.